Guided bone regeneration in the treatment of a compound odontoma in a dog - Marti, J. M.; Nalley, W. S.; Wallace, D. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
This case report describes the successful surgical treatment of a canine compound odontoma using guided bone regeneration. A five-month-old male Labrador cross dog was diagnosed with a compound mandibular odontoma. After surgical removal of the denticles and curettage of the lining of the bony cavity, a combination of autogenous cortico-cancellous bone graft and a bovine-derived, purified bone mineral matrix was packed into the defect. A resorbable collagen membrane was then secured over the graft and the gingival tissues sutured. Radiographs taken four months later revealed advanced graft incorporation and bony healing of the mandibular defect. A second surgery was necessary to remove redundant gingival tissue dorsal to the lesion. Eight months after the first operation, radiographs revealed complete bony union and remodeling of the mandibular ramus. It is concluded that grafting of compound mandibular odontomas can be a viable surgical alternative to other more aggressive procedures such as a partial mandibulectomy in the dog.A large mandibular compound odontoma was treated by curettage of the bony cavity, removal of denticles and placement of a combination of autogenous corticocancellous graft and demineralised bone matrix under a resorbable collagen membrane. A second operation was carried out to resect some exhuberant gingival tissue. This treatment restored the integrity of the mandibular bone and avoided aggresive surgical resection.
Keywords: Compound odontoma; bone grafting; guided bone regeneration